(3TQM aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3eG Tc aj eG JYfjg ajSJUMH chfG aj GdUdGI hjJaQY Ydjg MQeI EjLGO GdefGaj hdcf gPG GdGSJUMGH dG jLOj aj GMQGR GdeGehQ Hgs
(3BNQgG (B:s
(3BNQgG(B: (3abUO GdLRFjI aj GdYRjeI jhLH bUO GdSLhO dcfg dG jhLH bUO GdLRFjI ajg bhdg (B.. (3GdGTJZGd HGdhGLH hJMbjb GdRjGOI hCf SLhO GdYRjeI efgG djS ef hXjaI GdCUhdj hEfeG gh ef hGLH Gdabjgs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs